English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-10-23 02:59:49 · 4 answers · asked by Anonymous in Science & Mathematics Mathematics

doug_don...
no there is no equal sign after 3 it is a negative.

2007-10-23 03:08:59 · update #1

4 answers

3-(X^2-4)
= 3-X^2+4
= -X^2+7

2007-10-23 03:05:22 · answer #1 · answered by xmashi 3 · 0 0

I'm guessing that you meant 3 = (x+2)(x-2)
Do the indicated multiplication to get
3 = x² - 4 => x² - 7 = 0 so that
x² = 7 and x = ±√7

Doug

2007-10-23 10:06:26 · answer #2 · answered by doug_donaghue 7 · 0 0

3-(x+2)(x-2)= 3-(X^2-4)
= -X^2+7
7-X^2

2007-10-23 10:07:56 · answer #3 · answered by sathyanarayanan k 2 · 0 0

you first need to foil the two parenthesis.

3 - (x^2 - 4)

then distribute the negative into the parenthesis you have created

3 - x^2 +4

then combine like terms

7 - x^2 or -x^2 +7

2007-10-23 10:08:24 · answer #4 · answered by steve0stac 2 · 0 0

fedest.com, questions and answers